Discover the answers you need at Westonci.ca, a dynamic Q&A platform where knowledge is shared freely by a community of experts. Join our Q&A platform and get accurate answers to all your questions from professionals across multiple disciplines. Get quick and reliable solutions to your questions from a community of experienced experts on our platform.
Sagot :
To solve the equation
[tex]\[ \tan^{-1}(\ln(x^{2/3})) + \tan^{-1}(\ln(x^2)) + \tan^{-1}(\ln(x^2)) = \pi/2, \][/tex]
we start by simplifying each logarithmic term inside the inverse tangent functions.
Recall the logarithm properties: [tex]\( \ln(a^b) = b \ln(a) \)[/tex]. Applying this property:
1. [tex]\( \ln(x^{2/3}) = \frac{2}{3} \ln(x) \)[/tex]
2. [tex]\( \ln(x^2) = 2 \ln(x) \)[/tex]
Now rewrite the original equation using these logarithmic simplifications:
[tex]\[ \tan^{-1}\left(\frac{2}{3} \ln(x)\right) + \tan^{-1}(2 \ln(x)) + \tan^{-1}(2 \ln(x)) = \pi/2 \][/tex]
By combining the two identical terms:
[tex]\[ \tan^{-1}\left(\frac{2}{3} \ln(x)\right) + 2 \tan^{-1}(2 \ln(x)) = \pi/2 \][/tex]
Next, let [tex]\( y = \ln(x) \)[/tex]. Substituting [tex]\( y \)[/tex] into the equation:
[tex]\[ \tan^{-1}\left(\frac{2}{3} y\right) + 2 \tan^{-1}(2y) = \pi/2 \][/tex]
To simplify, assume [tex]\( a = \tan^{-1}\left(\frac{2}{3} y\right) \)[/tex] and [tex]\( b = \tan^{-1}(2y) \)[/tex]. Hence, the equation can be written as:
[tex]\[ a + 2b = \pi/2 \][/tex]
We use the identity for the sum of tangents for [tex]\(a\)[/tex] and [tex]\(b\)[/tex]:
[tex]\[ \tan(a + b) = \frac{\tan(a) + \tan(b)}{1 - \tan(a)\tan(b)} \][/tex]
Since [tex]\( \tan^{-1}(u) = a \)[/tex] implies [tex]\( \tan(a) = u \)[/tex]:
[tex]\[ \tan(a) = \frac{2}{3}y \quad \text{and} \quad \tan(b) = 2y \][/tex]
First, solve for [tex]\( \tan(a + b) \)[/tex]:
[tex]\[ \tan\left(a + 2b\right) = \tan\left(\frac{\pi}{2}\right) \rightarrow \text{undefined (since } \tan(\frac{\pi}{2}) \text{ is undefined)} \][/tex]
Therefore, for a valid solution as [tex]\( y \)[/tex]:
[tex]\[ a + 2b = \pi/2 \][/tex]
Let's assume simplifications to find [tex]\( y \)[/tex]:
Set [tex]\( \tan(a + b) = 1 \)[/tex]:
[tex]\[ \tan\left(\frac{\pi}{4}\right) = \frac{2y/3 + 2y}{1 - (2y/3)(2y)} = 1 \][/tex]
[tex]\[ 1 = \frac{(2y/3) + 2y}{1 - \frac{4y^2}{3}} \][/tex]
Solving this rational equation for [tex]\( y \)[/tex]:
[tex]\[ 1 = \frac{2y/3 + 2y}{1 - \frac{8y^2}{3}} \][/tex]
Cross-multiplying:
[tex]\[ 1 - \frac{8y^2}{3} = \frac{2y/3 + 2y} \][/tex]
Simplify and solve for [tex]\( y \)[/tex]:
[tex]\[ 1 - \frac{8y^2}{3} = \frac{8y/3} \][/tex]
Setting everything on one side:
[tex]\[ 1 = \frac{8y}{3} + \frac{8y^2}{3} \][/tex]
Multiply by 3:
[tex]\[ 3 = 8y + 8y^2 \][/tex]
Rearrange:
[tex]\[ 8y^2 + 8y - 3 = 0 \][/tex]
Solve this quadratic equation using the quadratic formula [tex]\( y = \frac{-b \pm \sqrt{b^2 - 4ac}}{2a} \)[/tex] where [tex]\( a = 8 \)[/tex], [tex]\( b = 8 \)[/tex], and [tex]\( c = -3 \)[/tex]:
[tex]\[ y = \frac{-8 \pm \sqrt{8^2 - 4 \cdot 8 \cdot (-3)}}{2 \cdot 8} \][/tex]
[tex]\[ y = \frac{-8 \pm \sqrt{64 + 96}}{16} \][/tex]
[tex]\[ y = \frac{-8 \pm \sqrt{160}}{16} \][/tex]
Simplify:
[tex]\[ y = \frac{-8 \pm 4\sqrt{10}}{16} \][/tex]
[tex]\[ y = \frac{-1 \pm \sqrt{10}}{4} \][/tex]
Only consider positive solutions for [tex]\( y \)[/tex]:
[tex]\[ y = \frac{\sqrt{10} - 1}{4} \][/tex]
Recall [tex]\( y = \ln(x) \)[/tex]:
[tex]\[ \ln(x) = \frac{\sqrt{10} - 1}{4} \][/tex]
Exponentiate both sides to solve for [tex]\( x \)[/tex]:
[tex]\[ x = e^{\frac{\sqrt{10} - 1}{4}} \][/tex]
Thus, the solution is:
[tex]\[ \boxed{e^{\frac{\sqrt{10} - 1}{4}}} \][/tex]
[tex]\[ \tan^{-1}(\ln(x^{2/3})) + \tan^{-1}(\ln(x^2)) + \tan^{-1}(\ln(x^2)) = \pi/2, \][/tex]
we start by simplifying each logarithmic term inside the inverse tangent functions.
Recall the logarithm properties: [tex]\( \ln(a^b) = b \ln(a) \)[/tex]. Applying this property:
1. [tex]\( \ln(x^{2/3}) = \frac{2}{3} \ln(x) \)[/tex]
2. [tex]\( \ln(x^2) = 2 \ln(x) \)[/tex]
Now rewrite the original equation using these logarithmic simplifications:
[tex]\[ \tan^{-1}\left(\frac{2}{3} \ln(x)\right) + \tan^{-1}(2 \ln(x)) + \tan^{-1}(2 \ln(x)) = \pi/2 \][/tex]
By combining the two identical terms:
[tex]\[ \tan^{-1}\left(\frac{2}{3} \ln(x)\right) + 2 \tan^{-1}(2 \ln(x)) = \pi/2 \][/tex]
Next, let [tex]\( y = \ln(x) \)[/tex]. Substituting [tex]\( y \)[/tex] into the equation:
[tex]\[ \tan^{-1}\left(\frac{2}{3} y\right) + 2 \tan^{-1}(2y) = \pi/2 \][/tex]
To simplify, assume [tex]\( a = \tan^{-1}\left(\frac{2}{3} y\right) \)[/tex] and [tex]\( b = \tan^{-1}(2y) \)[/tex]. Hence, the equation can be written as:
[tex]\[ a + 2b = \pi/2 \][/tex]
We use the identity for the sum of tangents for [tex]\(a\)[/tex] and [tex]\(b\)[/tex]:
[tex]\[ \tan(a + b) = \frac{\tan(a) + \tan(b)}{1 - \tan(a)\tan(b)} \][/tex]
Since [tex]\( \tan^{-1}(u) = a \)[/tex] implies [tex]\( \tan(a) = u \)[/tex]:
[tex]\[ \tan(a) = \frac{2}{3}y \quad \text{and} \quad \tan(b) = 2y \][/tex]
First, solve for [tex]\( \tan(a + b) \)[/tex]:
[tex]\[ \tan\left(a + 2b\right) = \tan\left(\frac{\pi}{2}\right) \rightarrow \text{undefined (since } \tan(\frac{\pi}{2}) \text{ is undefined)} \][/tex]
Therefore, for a valid solution as [tex]\( y \)[/tex]:
[tex]\[ a + 2b = \pi/2 \][/tex]
Let's assume simplifications to find [tex]\( y \)[/tex]:
Set [tex]\( \tan(a + b) = 1 \)[/tex]:
[tex]\[ \tan\left(\frac{\pi}{4}\right) = \frac{2y/3 + 2y}{1 - (2y/3)(2y)} = 1 \][/tex]
[tex]\[ 1 = \frac{(2y/3) + 2y}{1 - \frac{4y^2}{3}} \][/tex]
Solving this rational equation for [tex]\( y \)[/tex]:
[tex]\[ 1 = \frac{2y/3 + 2y}{1 - \frac{8y^2}{3}} \][/tex]
Cross-multiplying:
[tex]\[ 1 - \frac{8y^2}{3} = \frac{2y/3 + 2y} \][/tex]
Simplify and solve for [tex]\( y \)[/tex]:
[tex]\[ 1 - \frac{8y^2}{3} = \frac{8y/3} \][/tex]
Setting everything on one side:
[tex]\[ 1 = \frac{8y}{3} + \frac{8y^2}{3} \][/tex]
Multiply by 3:
[tex]\[ 3 = 8y + 8y^2 \][/tex]
Rearrange:
[tex]\[ 8y^2 + 8y - 3 = 0 \][/tex]
Solve this quadratic equation using the quadratic formula [tex]\( y = \frac{-b \pm \sqrt{b^2 - 4ac}}{2a} \)[/tex] where [tex]\( a = 8 \)[/tex], [tex]\( b = 8 \)[/tex], and [tex]\( c = -3 \)[/tex]:
[tex]\[ y = \frac{-8 \pm \sqrt{8^2 - 4 \cdot 8 \cdot (-3)}}{2 \cdot 8} \][/tex]
[tex]\[ y = \frac{-8 \pm \sqrt{64 + 96}}{16} \][/tex]
[tex]\[ y = \frac{-8 \pm \sqrt{160}}{16} \][/tex]
Simplify:
[tex]\[ y = \frac{-8 \pm 4\sqrt{10}}{16} \][/tex]
[tex]\[ y = \frac{-1 \pm \sqrt{10}}{4} \][/tex]
Only consider positive solutions for [tex]\( y \)[/tex]:
[tex]\[ y = \frac{\sqrt{10} - 1}{4} \][/tex]
Recall [tex]\( y = \ln(x) \)[/tex]:
[tex]\[ \ln(x) = \frac{\sqrt{10} - 1}{4} \][/tex]
Exponentiate both sides to solve for [tex]\( x \)[/tex]:
[tex]\[ x = e^{\frac{\sqrt{10} - 1}{4}} \][/tex]
Thus, the solution is:
[tex]\[ \boxed{e^{\frac{\sqrt{10} - 1}{4}}} \][/tex]
We hope our answers were helpful. Return anytime for more information and answers to any other questions you may have. We hope you found this helpful. Feel free to come back anytime for more accurate answers and updated information. We're glad you visited Westonci.ca. Return anytime for updated answers from our knowledgeable team.